Pattern recognition 12th Mexican Conference, MCPR 2020, Morelia, Mexico, June 24-27, 2020, proceedings /: 12th Mexican Conference, MCPR 2020, Morelia, Mexico, June 24-27, 2020, proceedings. (2020) - Unknown
No abstract available